2014
DOI: 10.1063/1.4871744
|View full text |Cite
|
Sign up to set email alerts
|

On the 60th anniversary of the Lifshitz-Kosevich theory

Abstract: The Landau band effects in the quantum magnetic oscillations and the deviations from the quasiclassical Lifshitz-Kosevich theory in quasi-two-dimensional conductors Low Temp. Phys. 37, 964 (2011);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…19, the shape of the MR curve is drastically different from the results discussed previously (Figs 17 and 18). Shubnikov-De Haas (SdH) oscillations analysis showed that the amplitude of the SdH oscillations increases with nitrogen concentration and linearly decreases with increasing temperature, persisting up to a temperature of 150 K. This dependence, at odds with the well-established Lifshitz-Kosevich theory [124,125], was tentatively explained by a dopants-induced bandgap which renormalizes the cyclotron mass and by a temperature dependence of the scattering time.…”
Section: Magnetoresistance Experiments On Chemically-doped Graphenementioning
confidence: 98%
“…19, the shape of the MR curve is drastically different from the results discussed previously (Figs 17 and 18). Shubnikov-De Haas (SdH) oscillations analysis showed that the amplitude of the SdH oscillations increases with nitrogen concentration and linearly decreases with increasing temperature, persisting up to a temperature of 150 K. This dependence, at odds with the well-established Lifshitz-Kosevich theory [124,125], was tentatively explained by a dopants-induced bandgap which renormalizes the cyclotron mass and by a temperature dependence of the scattering time.…”
Section: Magnetoresistance Experiments On Chemically-doped Graphenementioning
confidence: 98%
“…This is known as the De Haas-Van Alphen effect (dHvA) oscillations that originate from the orbital motion of itinerant electron at high magnetic fields [ 41 ]. We analyze the dHvA oscillations by fitting the oscillatory magnetization to the Lifshitz-Kosevich (LK) formula [ 42 ], . R is related to the carrier scattering rate, Zeeman effect, and Landau level broadening [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…At values of the magnetic fields where the effect of the periodic atomic lattice sites dominates, the effect of the magnetic fields can be described simply in terms of the dynamics of the Bloch energy bands [12,13] . For example, for finite magnetic fields, this is manifested in de Haas-van Alphen effects [14,15] due to Landau orbits at the Fermi surface, and magnetic breakdown between orbits in complicated Fermi surfaces in metals [16,17]. For smaller magnetic fields, the Bloch-band dynamics is manifested in such phenomena as paramagnetic and diamagnetic susceptibility.…”
Section: Low Finite Fieldsmentioning
confidence: 99%